Perencanaan Strategis Sekolah Penggerak dalam Pengembangan SDM Untuk Implementasi Kurikulum Merdeka - Setyati, Widji; Wuryandini, Endang; Br Ginting, Rosalina (Jayapangus Press, 2025)
The Merdeka Curriculum was initially implemented by Sekolah Penggerak which possess distinct characteristics and require all teachers to be well-prepared in both understanding and applying the curriculum. This study aims to analyze the strategic planning of human resource development for the implementation of the Merdeka Curriculum at SD Negeri Batursari 5. A qualitative descriptive method was employed, with data collected through interviews, observations, and document analysis. Data validity was ensured using triangulation, while data analysis involved data condensation, presentation, and conclusion drawing. The findings reveal that the principal formulated a strategic plan involving all school stakeholders through six stages, (1) establishing the school's vision, mission, and goals; (2) conducting internal analysis (strengths and weaknesses), (3) conducting external analysis (opportunities and threats, (4) formulating policies and strategies, (5) conducting evaluation and reflection and (6) follow-up actions based on the evaluation and reflection. The study concludes that strategic planning for human resource development is essential to ensure the successful implementation of the Merdeka Curriculum.